Space heating operation of combination boilers in the UK: The case for addressing real-world boiler performance. (January 2019) - Bennett, George; Elwell, Cliff; Oreszczyn, Tadj
Residential space and water heating account for 23% of UK final energy demand and combination gas boilers are the dominant technology. Performance gap issues in gas boiler systems have been reported, with previous studies unable to isolate or quantify root causes for performance issues, hampered by indirect and coarse measurement methods. Utilising high-frequency data, through state-of-the-art boiler diagnostics from 221 UK combination boilers, assumptions in efficiency standards are challenged. Total heating energy consumption and number of hot water tappings are in line with national expectations but the observed cycling behaviour of boilers gives cause for concern due to links with lower performance and higher emissions. Most combi-boilers appear oversized for space heating and despite available modulation are unable to prevent rapid on–off cycling. Per day, half of combi boilers studied average more than 50 starts and 70% of starts average less than 10 min during space heating operation. Cycling contradicts assumptions in efficiency testing standards, which assume steady state operation, weighted by full and part power measurements. Addressing oversizing and excessive boiler cycling provides an opportunity to quickly and significantly reduce emissions associated with heating, at low cost through the ongoing replacement of millions of boilers. Practical application: Lessons learned from this research regarding the detrimental performance issues seen in gas combi boilers are directly applicable to the topics of boiler specification for building service engineers and installers, such as guidelines in CIBSE Guide A, 1 CE54 Whole house boiler sizing method 2 and legislation set out in BoilerPlus from the Department of Business, Energy and Industrial Strategy. Plant size ratio, radiator hydraulic layout and controls can all contribute to the rapid cycling seen in the data and can all be influenced by building service professionals. Boiler modulation range is also crucial and manufacturers need to be aware of the benefits of extending modulation in new products.